Gestes et formes esthétiques désobéissants. - Mathieu Corp (Amnis)
Initiated by an act of civil disobedience during October 2019, the estallido social chileno ("Chilean social explosion") quickly became a massive mobilization, interrupted in March 2020 by the measures restricting freedoms imposed by Sebastián Piñera's government to curb the Covid-19 pandemic. One of the singular features of this social mobilization is the diversity and recurrence of the gestures and interventions implemented in public space, sharing certain characteristics of so-called acts of civil disobedience and drawing on aesthetic and artistic resources: from iconoclastic gestures implemented on statues and monuments, to performances organized by various feminist collectives, to light projections by the Delight Lab collective. Heterogeneous in their forms, protagonists and functions – critical, prospective or interpellative – these interventions contributed to the spectacularization and mediatization of the social movement, feeding the dissensus from which it proceeded.